1998
DOI: 10.1002/(sici)1099-1077(199808)13:6<413::aid-hup12>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

The safety of risperidone: a post-marketing study on 7684 patients

Abstract: Risperidone is a relatively new antipsychotic agent licensed for the treatment of schizophrenia and other psychotic conditions in patients aged 15 years or older. This study examines the safety of risperidone used in general practice. Information was collected for 7684 patients included in a non-interventional observational cohort study conducted by means of Prescription-Event Monitoring. Incidence rates were calculated to rank the frequency of reported events. Drowsiness/sedation was the most frequent reason … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…In one placebo-controlled study, patients receiving sertindole 12 mg actually experienced less sedation than those in the placebo group (Zimbroff et al 1997). A recent, post-marketing, observational study of over 7500 patients prescribed risperidone revealed that the adverse events most often leading to discontinuation of treatment were drowsiness and sedation (Mackay et al 1998). …”
Section: Sedationmentioning
confidence: 46%
See 1 more Smart Citation
“…In one placebo-controlled study, patients receiving sertindole 12 mg actually experienced less sedation than those in the placebo group (Zimbroff et al 1997). A recent, post-marketing, observational study of over 7500 patients prescribed risperidone revealed that the adverse events most often leading to discontinuation of treatment were drowsiness and sedation (Mackay et al 1998). …”
Section: Sedationmentioning
confidence: 46%
“…Post-marketing studies have been conducted for risperidone (Mackay et al 1998) and sertindole (Lundbeck A/S 1999). The results from these studies reveal a higher clinically significant rate of all-cause mortality for risperidone than for sertindole (Table 8).…”
Section: Mortality In Post-marketing Studiesmentioning
confidence: 99%
“…In a recent report describing two cases of risperidone treatment before and throughout pregnancy, no complications were observed (Ratnayake and Libretto, 2002). This is in agreement with the findings of a postmarketing study of 7684 patients who were prescribed risperidone (Mackay et al, 1998). Among nine pregnant women treated with risperidone there were seven live births and three therapeutic terminations; no abnormalities were reported among the seven live children exposed in utero to the drug.…”
Section: A Antipsychotic Drugsmentioning
confidence: 99%
“…Haloperidol and risperidone were significantly more potent than sertindole; olanzapine and clozapine were less potent. Noteworthy, the all-cause mortality rate for sertindole-treated patients was less than half that for risperidonetreated patients, and also considerably lower than that for olanzapine-treated patients (Mackay et al, 1998). The QTprolonging potency of sertindole was equivalent to that of its metabolites Lu 28 -092 and Lu 25-073 (Drici et al, 1998).…”
Section: Effects Of Sertindole On Myocardial Repolarizationmentioning
confidence: 99%